Post-Traumatic Arteriovenous Fistula of the Scalp - Ki, Hee Jong (J Korean Neurosurg Soc, 2015)
Arteriovenous fistula of the scalp is relatively rare disease. We report a traumatic arteriovenous fistula of the scalp treated with complete surgical excision and review the literature with regard to etiology, pathogenesis, and management of these unusual lesions.